Corporate Governance and Its Influence on Financial Performance: Evidence from the Banking Sector - Haruto Tanaka; Priya Kumar; Tanaki Kagura (International Journal of Economics, Commerce, and Management, 2024)
This research investigates the impact of corporate governance practices on the financial performance of banks. By analyzing data from various banking institutions, the study reveals that effective governance mechanisms, such as board diversity and regulatory compliance, positively influence profitability and risk management. The results provide insights into how banks can enhance their performance through improved governance structures.